Anosmia and ageusia are emerging as symptoms in patients with COVID-19: What does the current evidence say? - Russell, Beth; Moss, Charlotte; Rigg, Anne; Hopkins, Claire; Papa, Sophie; Van Hemelrijck, Mieke (Ecancermedicalscience, 2020)
There have been several reports noting anosmia and ageusia as possible symptoms of COVID-19. This is of particular interest in oncology since patients receiving some cancer treatments such as chemotherapy or immune therapy often experience similar symptoms as side-effects. The purpose of this report was to summarise the evidence on the existence of anosmia and ageusia an emerging COVID-19 symptoms in order to better inform both oncology patients and clinicians. Currently, there is no published evidence or case reports noting anosmia or ageusia as symptoms of COVID-19. Nevertheless, experts in rhinology have suggested that the onset of such symptoms could either act as a trigger for testing for the disease where possible, or could be a new criterion to self-isolate. Whilst more data is currently needed to strengthen our knowledge of the symptoms of COVID-19, oncology patients who are concerned about anosmia or ageusia in the context of their systemic anti-cancer therapy should contact their acute oncology support line for advice.